2002
DOI: 10.1161/hyp.39.2.614
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Damage Prevention by Eplerenone: Comparison With Low Sodium Diet or Potassium Loading

Abstract: To determine the extent to which dietary sodium modulates aldosterone-induced cardiovascular damage, and to determine whether increased dietary potassium can prevent this damage, we used the Nω -nitro- l -arginine methyl ester (L-NAME)/angiotensin II (Ang II) rat model of cardiac injury. This model is dependent on the presence of aldosterone for the occurrence of myocardial damage. Two sets of experiments were performed. In the first set, the following groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 20 publications
3
64
1
1
Order By: Relevance
“…Eplere- none prevented cardiac damage without reducing systolic BP in l-NAME (inhibitor of the nitric oxide synthesis)/Ang II treated rats at either low or high sodium diet [24]. In the present study, although eplerenone or enalapril partially prevented the progressive increase of BP, the combined therapy was more effective for the antihypertensive effect.…”
Section: Discussioncontrasting
confidence: 48%
“…Eplere- none prevented cardiac damage without reducing systolic BP in l-NAME (inhibitor of the nitric oxide synthesis)/Ang II treated rats at either low or high sodium diet [24]. In the present study, although eplerenone or enalapril partially prevented the progressive increase of BP, the combined therapy was more effective for the antihypertensive effect.…”
Section: Discussioncontrasting
confidence: 48%
“…In the L-NAME/Ang II animal model, dietary potassium supplementation does not prevent the development of cardiac damage, suggesting that the beneficial effects of MR antagonists are not mediated by increases in body potassium stores [20]. Similarly, potassium supplementation does not reduce cardiovascular injury in the aldosterone-infused uninephrectomized rat model [9].…”
Section: Dietary Potassiummentioning
confidence: 97%
“…This dependence on dietary sodium intake is illustrated by the finding that L-NAME/Ang II animals fed a low-salt diet do not develop vascular damage. Furthermore, the lack of damage occurs in the setting of a 10-fold increase in plasma aldosterone levels compared to animals on a high-salt diet suggesting that blood levels of aldosterone are not a good predictor of aldosterone-mediated vascular injury [20].…”
Section: Dietary Sodiummentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several other mechanisms of action should be considered, such as the blockade of the nonepithelial, MR-mediated effects of aldosterone in the heart and blood vessels. The recent availability of the SARA eplerenone has shown that, in a rat model of cardiac injury, treatment with this compound prevented the development of cardiac damage and exerted significant renal protective effects [44,45]. More recently, the EPHESUS study has evaluated treatment with eplerenone initiated during the acute phase of MI among patients with LV ejection fraction (LVEF) <40% [9•].…”
Section: Essential Hypertension Aldosterone and Aldosterone Antagonmentioning
confidence: 99%